ANALISIS PENGARUH TINGKAT LITERASI KEUANGAN TERHADAP PENGELOLAAN KEUANGAN PADA PELAKU UMKM DI GUNUNGSARI - Silpya Raudatul Ulfiany; Herlina Pusparini; Nurabiah Nurabiah (Jurnal Riset Mahasiswa Akuntansi, 2023)
This study aims to determine the effect of financial literacy level on financial management in MSME actors in Gunungsari District. The type of research used in this study is associative with a quantitative approach. The sample set in this study is 35 units of Micro, Small and Medium Enterprises (MSMEs) made from wood, bamboo and rattan with a total of 70 respondents in Gunungsari District. The data collection technique in this study was a questionnaire. The results showed that financial literacy has a positive and significant effect on financial management. So this indicates that the higher the level of financial literacy owned, the better the financial behavior.